Antibody-Based Detection of ERG Rearrangement-Positive Prostate Cancer - Park, Kyung (Neoplasia Press Inc., 2010)
TMPRSS2-ERG gene fusions occur in 50% of prostate cancers and result in the overexpression of a chimeric fusion transcript that encodes a truncated ERG product. Previous attempts to detect truncated ERG products have been hindered by a lack of specific antibodies. Here, we characterize a rabbit anti-ERG monoclonal antibody (clone EPR 3864; Epitomics, Burlingame, CA) using immunoblot analysis on prostate cancer cell lines, synthetic TMPRSS2-ERG constructs, chromatin immunoprecipitation, and immunofluorescence. We correlated ERG protein expression with the presence of ERG gene rearrangements in prostate cancer tissues using a combined immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) analysis. We independently evaluated two patient cohorts and observed ERG expression confined to prostate cancer cells and high-grade prostatic intraepithelial neoplasia associated with ERG-positive cancer, as well as vessels and lymphocytes (where ERG has a known biologic role). Image analysis of 131 cases demonstrated nearly 100% sensitivity for detecting ERG rearrangement prostate cancer, with only 2 (1.5%) of 131 cases demonstrating strong ERG protein expression without any known ERG gene fusion. The combined pathology evaluation of 207 patient tumors for ERG protein expression had 95.7% sensitivity and 96.5% specificity for determining ERG rearrangement prostate cancer. In conclusion, this study qualifies a specific anti-ERG antibody and demonstrates exquisite association between ERG gene rearrangement and truncated ERG protein product expression. Given the ease of performing IHC versus FISH, ERG protein expression may be useful for molecularly subtyping prostate cancer based on ERG rearrangement status and suggests clinical utility in prostate needle biopsy evaluation.